Contextual clues Pow Toon for flipped classroom / Siti Ainul Ayzan Ayub ...[et al.] - Ayub, Siti Ainul Ayzan; Wan Mohamed, Wan Nazihah; Abdul Malek, Nur Ain; Kamarudin, Hanis (2018)
Reading is an important skill to master but many English for Second Language (ESL) students are facing difficulties particularly in the area of contextual clues. The challenge in teaching contextual clues is that the current teaching method has lost its way to cater students’ interest in reading. In line with the latest revolution in teaching and learning method, the emergence of PowToon has helped to ease the process of teaching reading skills. Its features which include captivating graphics, lively animation, concise content and attractive background music will help the learning process to be more interesting. Using PowToon as flipped classroom material, students view the language content in mobile phones outside the classroom session which allows them to enjoy meaningful language classes at their own pace. In addition, it assists the students to familiarize themselves with the content before attempting various activities to enhance knowledge while receiving support from lecturers during classroom session. Acessible to everyone; online and offline, this product is user friendly and suitable to be used in language classes with limited technology support. This evolution in teaching pedagogy will also encourage paperless teaching aids in language classrooms. Hence, this blended learning strategy aims in increasing students’ engagement in reading and improving the outcomes of learning process.